Santa María Micaela Housing Cooperative in Valencia: a Critical Assimilation of the Modern Legacy - Jordá, Carmen; Palomares, Maite (Docomomo Journal, 2014)
The history of Valencian architecture reached one of its highest points with a project for the Cooperativa de Agentes Comerciales, consisting of a group of 138 dwellings (1958–1961) on the corner between Pérez Galdós Avenue and Santa María Micaela Street, after which this complex is named. It is a residential complex unique for its early and conscious association with a distinct modernity that would not be limited only to the national setting, as we shall see. We only have to consider some of the leading works of that period, which revived the contributions of the grand masters, Le Corbusier being the main focus, but not forgetting Mies van der Rohe. Indeed, the critical analyses undertaken by the Team X group, as well as the interpretations of the modern legacy that the Latin American architects undertook, are well known.